PROTECTIVE EFFECT OF ZILEUTON AND MK-866 AGAINST HEPATIC DAMAGE INDUCED BY DOXORUBICIN - H SAHIB, HUSSAM; M SULTAN, AHMED; A SAHEB, HUSSEIN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study was designed to investigate the protective effect of Zileuton and MK-886 against hepatic damage induced by doxorubicin. Methods: A total of 30 healthy adult male albino rats were randomized and rats were divided into five groups, six animals in each: Control negative group, Vehicle group: Rats were given ethanol i.p., Dx group: Doxorubicin (15 mg/kg), Mk group: Mk-886-treated rats given 0.6 mg/kg of Mk-886 i.p, and Z group: Zileuton-treated rats given zileuton 10 mg/kg i.p. Biochemical tests of the serum for ASAT and ALAT level were estimated. Serum glutathione (GSH) concentrations (μg/ml) were determined using GSH ELISA Kit, while serum malondialdehyde (MDA) concentrations (ng/ml) were determined using MDA ELISA Kit. Livers were removed from each rat and fixed in 10% neutral-buffered formalin and embedded in paraffin for histopathological studies. Results: MK- and zileuton-treated groups showed higher GSH levels and lower MDA levels as compared with Dx-treated group. MK-886 associated with significant p<0.05 decreased the liver enzymes in comparison with doxorubicin-treated rats. Zileuton showed insignificant (p>0.05) changes. The liver tissues that treated with Dx only showed several histopathological changes such as moderate sinusoidal dilation, vacuolation, mild-to-moderate hepatocyte necrosis/degeneration and inflammatory cell infiltration, and severe congestion. Liver tissues that treated by zileuton with Dx showed sinusoidal dilation, vacuolation, mild congestion, and inflammatory cell infiltration, while those treated with Mk-886 plus Dx showed nearly normal liver pathophysiology. Conclusion: It has been concluded that Zileuton and MK-886 have protective effects against hepatic damage induced by doxorubicin.